Experimental Validation of Basic Natural Ventilation Air Flow Calculations for Different Flow Path and Window Configurations. (November 2015) - Erhart, T.; Guerlich, D.; Schulze, T.; Eicker, U.
Abstract: Natural ventilation is applied to realise the hygienic minimum air exchange, to protect from moisture damages and to provide good thermal comfort by intensive summer ventilation. Considering energy efficient buildings without mechanical cooling and ventilation, the air exchange rate provided by window ventilation is a crucial design variable. Simple analytical volume flow calculation allows the determination of air change rates for various window opening configurations and types under static conditions. This work first introduces the calculation method of a planning tool developed in the context of the 'KonLuft' project. With that tool common opening geometries and natural ventilation flow path configurations can be planned for residential and non-residential buildings. The very focus is on the validation of the analytical calculation method via full-scale traces-gas (TG) measurements for different window configurations. The investigations were carried out with a comprehensive monitoring system in one corner room of a historical office building in the city center of Stuttgart. The window types examined are bottom-hung and side-hung windows. A mismatch factor of approximately 2 between the field experiment and the calculation is explained via a literature reference performing laboratory measurements. Hence it is advisable to take the local prevalent flow situation into account for calculations of volume flow.